1986
DOI: 10.1523/jneurosci.06-09-02578.1986
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of beta-adrenergic receptors and adenylate cyclase in coated vesicles isolated from bovine brain

Abstract: To assess whether internalization of beta-adrenergic receptor occurs in the CNS, we have isolated clathrin-coated vesicles from bovine forebrain and examined them for the presence of beta-adrenergic receptor binding and adenylate cyclase activities. A coated vesicle enriched preparation isolated by successive D2O-Ficoll density gradient centrifugations was applied to a glass bead permeation column to achieve further purification. Two major peaks of protein were eluted from the column and monitored by electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
1

Year Published

1987
1987
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 21 publications
3
19
1
Order By: Relevance
“…The similarity in the expression pattern of the common alpha and beta subunits of G-proteins in CV to the one typical of bovine brain demonstrates that CV play a role in the subcellular transport of these guanine nucleotide regulatory proteins. The results are also consistent with studies that showed the presence of adenylate cyclase activity in brain CV (3,5,6). These findings suggest that receptors and their transduction machinery are co-transported in CV during their export or internalization in neurons.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The similarity in the expression pattern of the common alpha and beta subunits of G-proteins in CV to the one typical of bovine brain demonstrates that CV play a role in the subcellular transport of these guanine nucleotide regulatory proteins. The results are also consistent with studies that showed the presence of adenylate cyclase activity in brain CV (3,5,6). These findings suggest that receptors and their transduction machinery are co-transported in CV during their export or internalization in neurons.…”
supporting
confidence: 92%
“…Clathrin coated vesicles (CV) participate in the transport and recycling of hormones, cellu lar membranes and their constituent mole cules, i.e., receptors (1)(2)(3)(4)(5)(6)(7). In neuronal tis sue, CV have been shown to transport opiate, muscarinic, beta-adrenergic, alpha-adrenergic, and adenosine (Al) receptors (1,3,(5)(6)(7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, evidence for the presence of the components of the adenylate cyclase system such as receptors that mediate stimulation [16], receptors that mediate inhibition [ 17,181, the catalytic activity and Gproteins [l&19] have been described in coated vesicles. These are subcellular organelles involved in endocytotic and exocytotic protein trafficking within the cell [20].…”
Section: Introduction Phospholipase C (Plc)mentioning
confidence: 99%
“…,8-Adrenergic receptors have been reported to be present in coated vesicles and supposed to be internalized by the vesicles, leading to desensitization of this receptor on the plasma membrane (2). In addition, muscarinic acetyl choline (3), opioid (4), a2 -adrenergic (5) and adenosine receptors (6) have been demon strated to be present in the coated vesicles.…”
mentioning
confidence: 99%